The Role Of Human Resource Management Practices On Employee Performance (Case Study: PT. Angkasa Pura I (Persero) Branch Sam Ratulangi International Airport) - Lengkong, Palulungan, Kindangen, (JURNAL RISET BISNIS DAN MANAJEMEN, 2018)
Â The result shows that simultaneously, recruitment, selection, and training and development are positively and significantly influence employee performance. Partially, recruitment (X1) has a positive but not significantly influence employee performance, selection (X2) has a positive but not significantly influence employee performance, and training and development (X3) has a positive and very significantly influence employee performance (Y)Keywords: Recruitment, Selection, Training And Development, Â Employee Performance